Pancreatitis (Inflammation Of The Pancreas) - Ko’chiboyev Samandar Ismatulla Ogli; Oralov Dilshod Hamid Ogli; Mirzaqulov Sardor Ulug‘Bek Ogli; Ximmatov Jamshid Alisher Ogli (Zien Journals, 2025)
Pancreatitis is an inflammatory condition of the pancreas characterized by premature activation of pancreatic enzymes that lead to auto-digestion of pancreatic tissue. This article discusses the clinical manifestations, diagnostic approaches, and treatment protocols of acute pancreatitis, focusing on evidencebased and intensive care strategies. The content is compiled based on real clinical practices and scientific references
Keywords: pancreatitis; enzymes; amylase